Characterization and Testing the Efficiency of Acinetobacter baumannii Phage vB-GEC_Ab-M-G7 as an Antibacterial Agent - Kusradze, Ia; Karumidze, Natia; Rigvava, Sophio; Dvalidze, Teona; Katsitadze, Malkhaz; Amiranashvili, Irakli; Goderdzishvili, Marina (Frontiers in Microbiology, 2016)
Acinetobacter baumannii is a gram-negative, non-motile bacterium that, due to its multidrug resistance, has become a major nosocomial pathogen .The increasing number of multidrug resistant (MDR) strains has renewed interest in phage therapy. The aim of our study was to assess the effectiveness of phage administration in Acinetobacter baumannii wound infections in an animal model to demonstrate phage therapy as non-toxic, safe and alternative antibacterial remedy. Using classical methods for the study of bacteriophage properties, we characterized phage vB-GEC_Ab-M-G7 as a dsDNA myovirus with a 90kb genome size. Important characteristics of vB-GEC_Ab-M-G7include a short latent period and large burst size, wide host range, resistance to chloroform and thermal and pH stability. In a rat wound model, phage application effectively decreased the number of bacteria isolated from the wounds of successfully treated animals. This study highlights the effectiveness of the phage therapy and provides further insight into treating infections caused by MDR strains using phage administration.